PEDAGOGI FEMINIS DALAM PEMBELAJARAN IPS - Melinda, Cicilia; Nana Supriatna (Journal Education Innovation (JEI), 2024)
Feminist pedagogy is a strategy to achieve the value of gender equality in education. Patriarchal culture in Indonesia differentiates women from men based on gender. So it is necessary to implement learning with feminist pedagogy in learning at school. When this is implemented, not only women or students will have a better life, but men (students) and children will also have a more peaceful life without discrimination and this is linked to social studies learning. This article examines gender awareness in the world of education. Feminism pedagogy in education and feminist pedagogy in social studies learning in Indonesia. This article is the result of a literature study taken from various journals about feminism. And it is hoped that it can become a useful gender study for social studies learning in secondary schools and universities.